Therapeutic prospects of nectin-4 in cancer: applications and value - Li, Kaiyue; Zhou, Yujing; Zang, Maolin; Jin, Xin; Li, Xin (Frontiers in Oncology, 2024)
Nectin-4 is a Ca2+-independent immunoglobulin-like protein that exhibits significantly elevated expression in malignant tumors while maintaining extremely low levels in healthy adult tissues. In recent years, overexpression of Nectin-4 has been implicated in tumor occurrence and development of various cancers, including breast cancer, urothelial cancer, and lung cancer. In 2019, the Food and Drug Administration approved enfortumab vedotin, the first antibody–drug conjugate targeting Nectin-4, for the treatment of urothelial carcinoma. This has emphasized the value of Nectin-4 in tumor targeted therapy and promoted the implementation of more clinical trials of enfortumab vedotin. In addition, many new drugs targeting Nectin-4 for the treatment of malignant tumors have entered clinical trials, with the aim of exploring potential new indications. However, the exact mechanisms by which Nectin-4 affects tumorigenesis and progression are still unclear, and the emergence of drug resistance and treatment-related adverse reactions poses challenges. This article reviews the diagnostic potential, prognostic significance, and molecular role of Nectin-4 in tumors, with a focus on clinical trials in the field of Nectin-4-related tumor treatment and the development of new drugs targeting Nectin-4.